2004
DOI: 10.1377/hlthaff.w4.455
|View full text |Cite
|
Sign up to set email alerts
|

Effects Of Generic-Only Drug Coverage In A Medicare HMO

Abstract: Rising pharmacy costs and demand for prescription drug coverage for broader populations of seniors have resulted in the implementation of generic-only pharmacy benefits in Medicare health maintenance organizations (HMOs). The impact on cost and quality of care is unknown. We examined data for members of a California Medicare HMO whose coverage changed to a generic-only benefit and found that the change was associated with reduced health plan pharmacy cost, increased out-of-pocket pharmacy costs for members, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 9 publications
2
18
0
Order By: Relevance
“…A restrictive drug policy in California led to decreases in the use of ACE-I and statins among high-risk cardiac patients which led to increased hospitalizations. 32 Similarly, costcontainment policies used in New Hampshire during the 1980s led to marked reductions of the use of essential drugs, particularly among the elderly, which led to increased use of health-care resources. 33,34 Recently, a limited-use policy for clopidogrel was shown to reduce the use of this drug and was associated with worse outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A restrictive drug policy in California led to decreases in the use of ACE-I and statins among high-risk cardiac patients which led to increased hospitalizations. 32 Similarly, costcontainment policies used in New Hampshire during the 1980s led to marked reductions of the use of essential drugs, particularly among the elderly, which led to increased use of health-care resources. 33,34 Recently, a limited-use policy for clopidogrel was shown to reduce the use of this drug and was associated with worse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Because medical therapy often represents a highly cost-effective strategy for chronic disease management, economic benefits obtained from limiting access to medications through restrictive policies may be lost because of increased use of health care resources and worse health outcomes over time. [32][33][34][35] A recent study has shown that a strategy of providing full unrestricted drug coverage for postmyocardial infarction patients would reduce mortality while also being highly cost-effective. 37 Alternatively, restrictive policies that decrease drug costs without affecting patient outcomes may represent an effective health care policy in light of limited health care budgets.…”
Section: Discussionmentioning
confidence: 99%
“…Generic formulations of alendronate may be less well tolerated than the proprietary preparations with a resulting poorer adherence to treatment [9]. Likewise, two studies in patients with diabetes and coronary disease showed that treatment plans to switch to generics led to significant reductions in the number of prescriptions, including angiotensin-converting enzyme (ACE) inhibitors and statins [10,11]. On the contrary, a recent study has reported that adherence to treatment was greater in patients who initiated on generics [12], and another has concluded that prescribing generic drugs for the treatment of hypercholesterolemia and diabetes was associated with a modest improvement of medication adherence [13], although this did not occur for antihypertensive drugs.…”
mentioning
confidence: 99%
“…Significant decreases were reported in the use of statin agents and antidepressant medications. 75 These results suggest that short-term decreases in pharmaceutical spending by payors may be offset by increased total medical costs.…”
Section: Patient Access To Proactive Therapies: the Impact Of Benefitmentioning
confidence: 98%